The morphosyntax of Gothic preverb compounds: incorporation and applicativisation - Tan, Tamisha L. (2024)
Gothic preverb compounds illustrate several interesting characteristics, including multiple preverb stacking, idiomatisation, tmesis (i.e., separation by clitics), and P-copying (i.e., multiple pronunciation of the preverb). This paper is a close examination of the morphosyntax of these compounds, highlighting novel empirical generalisations about the Gothic language with key theoretical implications for our understanding of Germanic complex verbs and the alternations they participate in. In particular, this paper proposes a structural distinction between preverb compounds which are obligatorily semantically transparent and those which are optionally idiomatic. In arguing that transparent compounds involve the mechanism of preposition incorporation and m-merger, paralleling recent accounts of clitic doubling, while idiomatic compounds involve a thematic high applicative projection, this paper captures nuanced differences in these compounds’ case assignment and argument licensing behaviour. These structural differences will be shown to derive these two compound types’ constrained interaction with the aforementioned phenomena of stacking, tmesis, and copying. In addition, this paper compares Gothic complex verbs to their cross-linguistic correlates within and beyond Germanic, whilst also providing a diachronic pathway for the development of (multiple) preverb compounds.